Implementasi Program Keluarga Harapan (PKH) di Nagari Kapeh Panji Jaya Talok pada Masa Pandemi Covid-19 - Ummi Kalsum; Adil Mubarak (Policy, Law and Political Research Center, 2022)
This study aims to determine the implementation of the Family Hope Program (PKH) in Nagari Kapeh Panji Jaya Talaok during the Covid-19 Pandemic. This research was carried out using a qualitative descriptive approach in which data collection was based on the factors that became the main supporters of the research object. In this study, the withdrawal of informants was based on a purposive sampling technique which was based on the main criteria, namely the people of Nagari Kapeh Panji Jaya Talaok. This data collection is done by means of interviews, observation and documentation. Data analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. Then the validity of this data was tested by triangulation of sources which was then analyzed. Based on the findings, it can be concluded that the Implementation of the Family Hope Program during the Covid-19 pandemic in Kapeh Panji Jaya Talaok can be said to be going well and the socialization carried out is still not effective because there are still people from the community who do not know the amount of assistance received, what It's just a requirement to become a KPM, and there are still people who abuse this assistance